CA-125 un error diagnóstico en tuberculosis peritoneal: Reporte de Caso: CA-125 a diagnostic error in peritoneal tuberculosis: Case Report (Revista Médica de Trujillo, 2023)
Case of peritoneal tuberculosis in a 54-year-old woman with a history of type II diabetes mellitus, treated irregularly; who presented a clinical picture of abdominal distension, low weight, hyporexia, and diffuse ascites associated with omental edema. A CA-125 sample was taken with a presumed diagnosis of ovarian cancer, however, pathological studies by laparoscopy reported chronic granulomatous peritonitis of the tuberculoid type with caseous necrosis, referring to peritoneal tuberculosis, which is a rare diagnosis that represents 0 .1–0.5% of all cases of Tuberculosis. Peritoneal tuberculosis should be considered as one of the possible differential diagnoses in cases of patients presenting ascites with elevated serum CA-125 levels. However, to confirm the diagnosis it is necessary to obtain histological evidence that supports the presence of changes compatible with this disease. In these people, exploratory laparoscopy is a diagnostic alternative, even more so if the hypothesis of malignancy has not been definitively proven. This case report addresses the situation and literature review of peritoneal tuberculosis, its relationship with CA-125, and its relevance in the differential diagnosis of ovarian cancer.
Keywords: peritoneal tuberculosis; ovarian cancer; CA-125 antigen